PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN LAPTOP ASUS PADA MAHASISWA DI BANDAR LAMPUNG - Endah Dwi Utami; Intan Ferdina Pratiwi; Vicky F Sanjaya (LPPM - STIE SAKTI ALAM KERINCI, 2021)
This study aims to determine, test and analyze the effect of the independent variables Price and Product Quality on the dependent variable of Asus laptop purchasing decisions on students. The method used in the research is a questionnaire. The population in this study were students totaling 45 respondents. Statistical tests were carried out using PLS-based Structurel Equation Modeling. The validity test uses the loading factor value while the reliability test uses Cronbach's alpha, composite reliability and Average Variance Extracted (AVE) values. All proposed hypotheses are supported and significant. The conclusion of this study is that the effect of price and product quality has a significant effect on purchasing decisions for Asus laptops.